Optimalisasi Konsep Manajemen Penilaian dalam Mendukung Studi Lanjut dan Perencanaan Masa Depan - Habsy, Bakhrudin All; Nashihah, Durrotun; Sari, Wahyu Asri Nur Tri Via; Sari, Siska Amelia (TSAQOFAH, 2024)
Assessment management is an important process that optimizes resources to achieve program goals effectively and efficiently. This research examines assessment management and further study. The method used is library research, with qualitative analysis of related literature. The results show that assessment management serves to measure the effectiveness of educational programs through accurate data. Assessment in the field of education, especially in guidance and counseling and further study selection, has a very important role, both to measure the success of the program and to help students make the right decisions regarding their further studies. The assessment mechanism is carried out to be able to ensure that the program runs effectively and further study decisions are made based on careful consideration.